Public health impact of adjuvanted RSVPreF3 vaccine in older adults: a modeling study in nine countries in Middle East and North Africa - Evelina Zimovetz; Abdullah M. Assiri; Sara Al Dallal; Desirée van Oorschot; Adriana Guzman-Holst; Jorge A. Gomez; Ru Han (Expert Review of Vaccines)
Background The adjuvanted RSV prefusion F protein vaccine (adjuvanted RSVPreF3) can protect older adults against respiratory syncytial virus (RSV) infection and RSV-related lower respiratory tract disease (LRTD). We modeled the burden of RSV and the potential public health impact of RSV vaccination in adults ≥60 years in nine countries of the Middle East and North Africa (MENA) region.Research design and methods A Markov model was adapted to the settings of Bahrain, Egypt, Saudi Arabia, Kuwait, Morocco, Oman, Qatar, Turkey, and the United Arab Emirates. RSV acute respiratory infection (ARI) cases, LRTD-related pneumonia, hospitalizations, and deaths were computed over a five-year time horizon assuming no vaccination, and assuming adjuvanted RSVPreF3 vaccination coverage rates of 30% and 70%. Sensitivity of key inputs was explored using one-way sensitivity analyses.Results Across the considered countries, 9.1 million RSV ARI cases, including 4.6 million LRTD, were projected in adults ≥60 years over 5 years. A 30% coverage with a single dose of adjuvanted RSVPreF3 would prevent 1,052,191 RSV ARI cases (including 677,794 LRTD), 56,642 hospitalizations 52,138 pneumonia cases, and 5,377 deaths.Conclusions An important part of the substantial RSV burden in adults ≥60 years in the selected MENA countries could be prevented through vaccination with adjuvanted RSVPreF3.